Between compassion, anger, resignation, and rebellion: Vocational civics teachers and their struggle to fulfil the intentions of the civics subject - Ekström, Linda (JSSE - Journal of Social Science Education, 2024)
Highlights: – Civics teachers face challenges in offering male vocational students quality citizenship education. – Civics teachers perceive this student group as vulnerable and in need of extra support. – When unable to offer desired civics education, teachers feel angry and resigned. – Civics teachers are willing to bend certain rules to support this particular student group. – If this student group lacks better civics education, their future and Sweden's democracy are at risk. Purpose: This paper examines how vocational civics teachers navigate structural constraints and their understanding of the challenges involved in preparing vocational students for democratic citizenship. Design/methodology/approach: Using a discoursive psychological approach to analyse interview material, the study discusses identified discourses about critical policy analysis and street-level bureaucracy theory. Findings: The findings reveal that the structure of vocational upper-secondary education significantly constrains civics teachers. Teachers oscillate between feelings of compassion, anger, resignation, and rebellion as they attempt to manage these challenges. Research limitations/implications: The study highlights the need for further ethnographic research on teaching practices. Practical implications: A significant number of Swedish upper-secondary students receive a limited civics education that inadequately prepares them for democratic citizenship.